Vagus nerve stimulation decreases left ventricular contractility in vivo in the human and pig heart - Lewis, M E (Blackwell Science Inc, 2001)
1. Studies of the effect of vagus nerve stimulation on ventricular myocardial function in mammals are limited, particularly in the human. 2. The present study was designed to determine the effect of direct electrical stimulation of the left vagus nerve on left ventricular contractile state in hearts paced at 10 % above the natural rate, in anaesthetised pigs and anaesthetised human subjects undergoing open chest surgery for coronary artery bypass grafting. 3. Contractility of the left ventricle was determined from a series of pressure-volume loops obtained from a combined pressure and conductance (volume) catheter placed in the left ventricle. From the measurements a regression slope of the end-systolic pressure-volume relationship was determined to give end-systolic elastance (Ees), a load-independent measure of contractility. 4. In six anaesthetised open chest pigs, stimulation of the peripheral cut end of the left cervical vagus nerve induced a significant decrease in Ees of 26 ± 14 %. 5. In nine patients electrical stimulation of the left thoracic vagus nerve close to its cardiac branch resulted in a significant drop in Ees of 38 ± 16 %. 6. The effects of vagal stimulation were blocked by the muscarinic antagonist glycopyrronium (5 mg kg(−1)). 7. Administration of the β-adrenoreceptor antagonist esmolol (1 mg kg(−1)) also attenuated the effect of vagal stimulation, indicating a degree of interaction of vagal and sympathetic influences on contractility. 8. These studies show that in the human and pig heart the left vagus nerve can profoundly decrease the inotropic state of the left ventricular myocardium independent of its bradycardic effect.